Structural Evolution and its Implication for the Emplacement of Gold Deposit in the Central Part of Burkina Faso, West Africa - Ouedraogo, Gomdebziige Ernest; Kagambega, Nicolas; Sawadogo, Saga; Zongo, Hubert G.; Ouedraogo, Madi; Lompo, Martin (European Scientific Journal, ESJ, 2024)
In order to constrain the structural evolution in the central part of Burkina Faso and its implication for the emplacement of gold deposits, we undertook a structural mapping by coupling Landsat and aeromagnetic images interpretation to outcrop and core mapping followed by laboratory work. This approach reveals that the structural architecture in this locality mainly results from dextral transcurrent progressive deformation due to a NW-SE trending major stress. This architecture is similar to the Riedel-Tchalenko model. Initially, the dominant normal stress created an E-W constriction resulting in the development of N-S shear corridors. Subsequently, the tangential stress that took over this generated the progressive development of simple dextral shear zones with a NE-SW orientation that are locally taken up by ENE-WSW dextral shear bands associated with the Riedel’s R structures. As a result of the cooling of the crust, we are witnessing the formation of sinistral NW-SE and dextral NNE-SSW strike-slip faults, respectively, which corresponds to Riedel’s R’ structures and Tchalenko’s P structures. The development of NW-SE pre-Eburnean shear zones, particularly the N-S shear corridors, is synchronous with the circulation of gold-bearing fluids through the zone. However, the intersections of these directional corridors create zones suitable for gold concentration. Within these zones, ductile-brittle deformation following the emplacement of the shear bands has facilitated the remobilization and concentration of gold-bearing fluids within rocks with the appropriate rheological conditions. This is the case for Toega gold deposit.